Information for agricultural and rural development in ACP countries: new stakeholders, new media and priority themes: proceedings - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2001)
The priority areas highlighted by the seminar were the development of support programmes to improve...